The Effects of Smoking on Anterior Segment Parameters, Retinal Nerve Fiber Layer, and Pupillary Functions - Bengü Ekinci Köktekir; Saban Gönül; Berker Bakbak; Şansal Gedik; Kamile Marakoğlu (Türk Oftalmoloji Dergisi, 2014)
Objectives: To evaluate the alterations in the anterior segment parameters, retinal nerve fiber layer, and pupillary functions in smokers. Materials and Methods: In this case-control study, 45 eyes of 45 smokers and 45 eyes of 45 non-smoker control subjects were evaluated. All patients underwent measurement of anterior segment parameters with optical low coherence reflectometry (OLCR), mesopic and photopic pupillary diameter with an aberrometer device, retinal nerve fiber layer thickness with optical coherence tomography, and dry-eye assessment with Schirmer’s test. The results were compared with independent t-test by SPSS 16.0 Inc., and a p-value lower than 0.05 was determined as significant. Results: There was a significant difference between both groups in terms of mesopic pupil diameters that were measured with both OLCR and aberrometer device (p=0.03 and 0.02, respectively). Schirmer scores were also significantly decreased in smokers (p=0.001). The other measured parameters demonstrated no difference between smokers and non-smokers (p>0.05 for all). Conclusion: Smoking may affect pupillary functions, especially the mesopic pupillary diameter, and may cause a deficiency in pupil response under dark circumstances. (Turk J Ophthalmol 2014; 44: 11-4)